University Student Perceptions of the Impact of the Social Unrest in Hong Kong. Issue 5 (3rd September 2022) - Ong, Elsie; Chu, Sam
ABSTRACT: Social unrest has a significant impact on all citizens but for university students, little is known about how they thrived through this period with certain disconnection to social support while living in residential halls. Therefore, this study focused on the lived experiences of a group of university students and explored how the social unrest had affected them. Focus group interviews were conducted with 20 university students in Hong Kong. Using thematic analysis, the transcriptions were categorized into four themes: disruptions to daily routines, impact on psychological wellbeing, relationships, and coping strategies. It was revealed that reduced social connections during the unrest impacted their coping strategies and relationships, and emotional distress. This sheds implications on policymaking in residential halls and for university counselling services